Why heads matter in palaeoanthropology: The impacts and consequences of collecting skulls - Lauren Schroeder; Paige Madison; Rebecca R. Ackermann (South African Journal of Science)
This piece reflects on the importance of and focus on heads – especially the collecting of skulls and its impacts – in alpha taxonomy, biological anthropology, and Western science more broadly. We consider how the announcement and overall discovery story of the Taung Child revolutionised our understanding of hominin cranial evolution, but also fit within these skull-collecting objectives and contributed to the palaeoanthropological fixation on the skull. We contextualise this within the history of ‘physical’ anthropology in light of its initial goals in scientific racism, and consider how this process of skull collecting has become normalised in the discipline as a result of this history. As evidence for this, we quantify the possible effects of skull-collecting by collating available data on the number of skulls versus post-crania curated in a representative South African collection and compare the number of skulls versus post-cranial hominin fossils that form part of species hypodigms. We also explore how the ownership of skulls and ownership of narrative in the discipline have been intertwined throughout its history. Finally, we focus on how this early overemphasis on skulls, and especially brain size/intelligence, may have skewed our understanding of human evolution and contributed to ideas of human exceptionalism.